COMPARATIVE STUDY OF KINESIOTAPING VERSUS INTRINSIC MUSCLE STRENGTHENING AND CRYOTHERAPY IN THE TREATMENT OF CHRONIC PLANTAR FASCITIS - AKSHAY V. KHATAVKAR; PROF.TUSHAR J. PALEKAR; SOUMIK BASU (International Journal of Pharma and Bio Sciences, 2015)
Plantar fascitis is a common chronic overuse injury of the plantar fascia worldwide. A Comparative study was conducted with a total of 30 subjects where subjects were divided equally into two groups by lottery method. Patients in Group B received intrinsic muscle strengthening exercises and cryotherapy and the Group A received only Kinesiotaping.Each patient was assessed on day 1st i.e.pre-treatment and on day 7th i.e.post-treatment with Plantar fascitis pain scale (PFPS), Foot function index (FFI) and the changes in the Ultrasonography (USG). Group A and Group B were compared using Chi-square test and <s>the</s> Student t test. In relation to USG, PFPS and FFI, Group A shows lesser pain with the decreased plantar fascial thickness than Group B on Day 7, with the P value <0.001. Thus, this study concludes that, Group A shows significant improvement in all parameters than Group B.